Widespread hepatitis B virus genotype G (HBV-G) infection during the early years of the HIV epidemic in the Netherlands among men who have sex with men. Issue 1 (December 2016) - Cornelissen, Marion; Zorgdrager, Fokla; Bruisten, Sylvia; Bakker, Margreet; Berkhout, Ben; van der Kuyl, Antoinette
Abstract Background Hepatitis B virus (HBV) variants belong to different genotypes, A-J, whose worldwide distribution is linked with geography, probably because viral spread was associated with ancient human migrations. HBV genotype G (HBV-G) is an aberrant genotype with little sequence divergence, suggesting a recent origin. HBV-G is strongly associated with certain risk groups such as intravenous drug users (IDUs) and men who have sex with men (MSM), but hardly with geography. The origin and epidemiology of HBV-G remain unresolved, as is the disease association. Methods To estimate the prevalence and possible time of introduction of HBV-G into the MSM community in Amsterdam, the Netherlands, we have retrospectively analysed 226 blood serum samples from HBsAg positive MSM enrolled in the Amsterdam Cohort Studies (ACS) on HIV infection and AIDS dating from 1984 to 1999 using genotype-specific PCR assays. Results Of the 226 HBsAg-positive samples, 149 were HBV DNA positive. Of those, 104 were positive for HBV genotype A (HBV-A) and five for HBV-G, and 40 showed a dual infection with both HBV-A and HBV-G. Being HIV-infected was significantly associated with a reduced HBV DNA viral load in blood, but not with the prevalence of HBV-G. Early virus already contained stop codons in the precore region and a 36 bp insertion in the core gene which are the characteristics of HBV-G. Conclusions HBV-G was introduced before 1985 into the Amsterdam MSM community. Early isolates show very limited sequence variation, confirming a low evolutionary rate. HBV-G acquisition was independent of HIV infection, but being HIV-infected was significantly associated with a reduced HBV viral load in blood, indicating a beneficial effect of early HIV infection in controlling HBV replication.